Tradisi Ziarah Kubur di Sumenep - Khamsill Lailii (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Abstract: Sumenep society basically does not recognize a common burialplace, except for the urban community that was already difficult to obtainland for a family tomb. Each family own a particular location as a place tobury the bodies to family members who died, either in part garden soil andsoil tegalnya. One burial site, normally, reserved for family or extendedfamily breadth. In fact, there is also the tomb consists of only two pieces andare in a position attached to the neighboring house, though still within theboundaries of the land itself. The existence of the tombs were small andscattered in the yard of the population are found, especially in rural areas.Moreover, there is no rule stipulating that the bodies should be buried at adesignated spot. The most fundamental reason of the burial ground itself is sothat the souls (spirits) of the deceased can be fused with the ground so that itspresence is quiet and does not wander.